Terorisme Sebagai Konstruksi Politik: Titik Balik Benturan Antar Peradaban - yahya, Fathurrahman (UPT Publikasi Ilmiah, 2024)
The September 11, 2001, attacks on the World Trade Center in New York and the Pentagon in Washington, DC, United States, are considered the most devastating terrorist acts of the early 21st century. Thousands of lives were lost, highlighting terrorism as the most dangerous threat of this century. The international community was shocked that a superpower like the United States could be targeted by terrorists. President George W. Bush promptly declared a war on terrorism, identifying it as the most pressing national security threat. He launched a global diplomatic campaign to combat terrorism. Since then, terrorism has been a major issue and a topic of debate, raising questions about its definition as a criminal act. This paper aims to explain the definition of terrorism, which often carries political and ideological biases that harm specific communities, particularly the Muslim community. The sporadic and tendentious interpretation of terrorism is often linked to theological aspects, suggesting that acts of terror (i.e., terrorism) are part of Islamic teachings through the lens of jihad. By reviewing relevant academic sources, this paper finds that the definition of terrorism is not singular and is often biased. Given the lack of consensus, Jurgen Habermas's perspective on communication and dialogue is important for bridging gaps between religions and civilizations. Additionally, Jacques Derrida's approach requires a deconstruction of the language surrounding previous understandings to comprehend terrorism fully.